(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine cognitive barriers related to integral integrals. With this aim, a definite integral task (Definite Integral Task) prepared by the researcher and consisting of two questions is given to eight students from the Mathematics and Mathematics Education program in the City of Semarang who have received integral calculus courses. The data obtained from this study found cognitive barriers that students might have on course integral material.